Design of a compact antenna test range system based on reflectarray antenna. Issue 12 (18th October 2022) - Liu, Xumin; Yang, Yixin
Abstract: A compact antenna test range (CATR) system based on a planner stepped‐edged reflectarray antenna is proposed in this article. The parameters of the reflectarray antenna are determined by the design method of a single reflector system. Physical Optics (PO) method is used to calculate the unit phase of the reflectarray. The performance of the quiet zone is improved by optimizing the array shape. A 4320‐element reflectarray antenna with a dual‐ring structure is proposed and fabricated. The measured results show that the amplitude distribution of the designed reflectarray compact range is within ±1 dB, the phase distribution is within ±10°, and the cross‐polarization isolations are greater than 24 dB in the region of 50% at 10 GHz. The performance of the quiet zone is favorable for the usage of CATR systems.